(untitled) (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: 1. Brevi considerazioni introduttive - 2. L’identità liquida del gender - 3. La famiglia nell’ottica del gender - 4. Gender inclusive language, genitorialità e modelli educativi - 5. La sfida antropologica del gender - 6. I riflessi sulla famiglia naturale - 7. In somma. Beyond the male and female. The family among the colors of gender fluid ABSTRACT: Gender ideology considers a person’s sexual identity, as male or female, according to personal sense. Thus, sexual identity is not linked to anatomical genitality and can be changed several times during the lifetime according to one’s own desires and choices. This ideology was considered as a cause of the weakening or breaking of the natural family. Notably, family is deprived of its anthropological, community, generative and pedagogical foundation. That is why gender ideology represents a challenge to the family. Nevertheless an appropriate solution must be fund to protect Lgbtq+ couples, regardless of sexual identity, individual tendencies and personal conditions and especially without ideological claims.